Pyroptosis in Osteoblasts: A Novel Hypothesis Underlying the Pathogenesis of Osteoporosis - Tao, Zhengbo; Wang, Jinpeng; Wen, Kaicheng; Yao, Renqi; Da, Wacili; Zhou, Siming; Meng, Yan; Qiu, Shui; Yang, Keda; Zhu, Yue; Tao, Lin (Frontiers in Endocrinology, 2021)
Osteoporosis has become a worldwide disease characterized by the reduction in bone mineral density and the alteration of bone architecture leading to increased risk of fragility fracture. And an increasing number of studies have indicated that osteoblasts undergo a large number of programmed death events by many different causes in osteoporosis and release NLRP3 and interleukin (e.g., inflammatory factors), which play pivotal roles in contributing to excessive differentiation of osteoclasts and result in exaggerated bone resorption. NLRP3 is activated during pyroptosis and processes the precursors of IL-1β and IL-18 into the mature forms, which are released into the extracellular milieu accompanied by cell rupture. All of these compounds are the classical factors of pyroptosis. The cellular effects of pyroptosis are commonly observed in osteoporosis. Although many previous studies have focused on the pathogenesis of these inflammatory factors in osteoporosis, pyroptosis has not been previously evaluated. In this review, pyroptosis is proposed as a novel hypothesis of osteoporosis pathogenesis for the first time, thus providing a new direction for the treatment of osteoporosis in the future.